Implementasi Konsep Alam pada Interior Resort Hotel di Pulau Kaniungan - Sherly Setiadi; Laksmi Kusuma Wardani; David Tan Kayogi (Intra, 2019)
Kaniungan Island is an island located on the tip of the South Coast of Berau, Biduk-Biduk. Kaniungan Island has a very interesting natural beauty. The existence of this island is still new, so it has not been widely known by tourists. Besides that, lodging needs on this island are still few. The design of the resort's interior, provides facilities to support development that elevate the potential of maritime tourism in Biduk-Biduk subdistrict especially in Kaniungan Island. So that it is able to meet lodging accommodation needs and attract tourists to come and get to know the tours in the Biduk-Biduk. This design, there are several design stages, understand, observe, point of view, ideation, ideate, prototype, test, story telling, pilot and business model which is called design thinking. The design results obtained are the application of natural concepts with typical fern flower ornaments Borneo and the distinctive characteristics of the natural environment on Kaniungan Island can display the identity or character of resort hotels while at the same time answering user needs and attracting tourists to visit Kaniungan Island. The concept of nature is applied through the existence of lobby, cottage, restaurant, floating café, sitting area, shop, kitchen, buffet table area, toilet, prayer room, storage room, staff room and stage area.